Anti-corruption commissions: lessons for the Asia-Pacific region from a proposed Australian federal anti-corruption watchdog. Issue 4 (8th August 2019) - Rama, Marie dela; Lester, Michael
ABSTRACT: This paper reviews the experience of anti-corruption commissions in the region and argues that the debate on the establishment of a national anti-corruption body in Australia is dependent on the country's political culture, institutions and elites. Corruption and integrity coexist and are conceived as the obverse and converse, respectively, of a functional and dysfunctional system. Anti-corruption bodies in the Asia-Pacific region are compared against applicable global anti-corruption frameworks, policies and principles. The paper proposes a conceptual model for a National Integrity Ecosystem (NIE), premised on community values and trust and situates the Australian experience within such an ecosystem. A federal anti-corruption watchdog is the missing piece in Australia's institutional infrastructure. Its acceptance and effectiveness require difficult and sustained change in the underlying political culture of the country and its elites.